Characterization and functional analysis of a Relish gene from the Asian corn borer, Ostrinia furnacalis (Guenée). Issue 2 (1st September 2021) - Chen, Kangkang; Chen, Jiaqian; Tang, Tai; Jiang, Haobo; Han, Zhaoyang; Wang, Libao; Alradi, Mohamed F.; Lu, Shiqi; Wei, Xiangyi; Liu, Xu; Wei, Youheng; Feng, Congjing
Abstract: Pathogen‐induced host immune responses reduce the efficacy of pathogens used to control pests. However, compared to the well‐deciphered immunity system of Drosophila melanogaster, the immunity system of agricultural pests is largely unconfirmed through functional analysis. Beginning to unveil mechanisms of transcription regulation of immune genes in the Asian corn borer, Ostrinia furnacalis, we cloned the complementary DNA (cDNA) of a transcription factor Relish by rapid amplification of cDNA ends. The 3164 bp cDNA, designated Of‐Relish, encodes a 956‐residue protein. Bioinformatic analysis showed that Of‐Relish had a Rel homology domain, a predicted cleavage site between Q 409 and L 410, six ankyrin repeats, and a death domain. The response of Of‐Relish expression to the Gram‐negative bacteria Pseudomonas aeruginosa was sooner and stronger than to the Gram‐positive Micrococcus luteus . The antimicrobial peptide genes Attacin and Gloverin had similar expression patterns in response to the infections. Knockdown of Of‐Relish led to a decrease in Attacin and Gloverin messenger RNA levels, suggesting that Attacin and Gloverin were regulated by Of‐Relish . Together, the results suggested that Of‐Relish is a key component of the IMD pathway in O. furnacalis, involved in defense against P. aeruginosa through activation of Attacin and Gloverin . Research Highlights: We cloned and characterized a Relish gene in Ostrinia furnacalis (Guenée). The response of Of‐Relish expression to the Gram‐negative bacteria Pseudomonas aeruginosa was sooner and stronger than to the Gram‐positive Micrococcus luteus . Of‐Relish is a key component of the IMD pathway in O. furnacalis, involved in defense against P. aeruginosa through activation of Attacin and Gloverin . Abstract :